Tonic immobility and phenomenal consciousness in animals: a review - Woodruff, Michael L. (Frontiers in Psychology, 2025)
Tonic immobility (TI) is an innate, last-resort response to the presence of a predator, commonly referred to as feigning death or thanatosis. However, it is critical to distinguish death feigning from TI; the former encompasses a complex series of behaviors, with TI representing its final aspect. Given this complexity, death feigning is hypothesized to manifest a higher-order intentionality in animals. Considering that third-order and higher intentional states are correlated with some form of phenomenal consciousness, their presence in animals has significant implications for their conscious experiences. This hypothesis surrounding third-order and higher intentional states is subject to dispute, in part due to the lack of sufficient evidence indicating that the behaviors associated with death feigning, aside from TI, serve a protective function against predation. Evidence suggests that TI alone constitutes an effective mechanism for predator defense. It is posited that the cessation of TI by the prey organism signifies the presence of a first-order intentional state. Furthermore, it is proposed that behavioral indicators suggest that the termination of TI by the prey is linked to anoetic and potentially noetic consciousness. The relationship between TI and fear is also examined. It is contended that, within the framework of formulating hypotheses concerning the mechanisms of TI and developing experimental designs to test these hypotheses, fear should be characterized as an intervening variable. The conclusions derived from this analysis indicate that TI can occasionally function as an effective predator defense associated with primal sensory and anoetic consciousness. Its termination may imply the presence of noetic consciousness; however, self-reflective autonoetic consciousness appears to be absent. Finally, the hypothesis suggesting that TI serves as an evolutionary precursor to the theory of mind in humans is discussed, serving as a cautionary note in the interpretation of findings from animal research concerning the evolution of cognitive functions in humans.